Single‐Cell Multi‐omics Assessment of Spinal Cord Injury Blocking via Cerium‐doped Upconversion Antioxidant Nanoenzymes - Ke Wang; Judun Zheng; Ronghai Li; Tianjun Chen; Yanming Ma; Ping Wu; Jianxian Luo; Jingyi Zhu; Weiqiang Lin; Minghai Zhao; Yue Yuan; Wen Ma; et al. (Advanced Science)
Abstract Spinal cord injury (SCI) impairs the central nervous system and induces the myelin‐sheath‐deterioration because of reactive oxygen species (ROS), further hindering the recovery of function. Herein, the simultaneously emergency treatment and dynamic luminescence severity assessment (SETLSA) strategy is designed for SCI based on cerium (Ce)‐doped upconversion antioxidant nanoenzymes (Ce@UCNP‐BCH). Ce@UCNP‐BCH can not only efficiently eliminate the SCI localized ROS, but dynamically monitor the oxidative state in the SCI repair process using a ratiometric luminescence signal. Moreover, the classic basso mouse scale score and immunofluorescence analysis together exhibit that Ce@UCNP‐BCH effectively facilitates the regeneration of spinal cord including myelin sheath, and promotes the functional recovery of SCI mice. Particularly, the study combines snATAC‐eq and snRNA‐seq to reveal the heterogeneity of spinal cord tissue following Ce@UCNP‐BCH treatment. The findings reveal a significant increase in myelinating oligodendrocytes, as well as higher expression of myelination‐related genes, and the study also reveals the gene regulatory dynamics of remyelination after treatment. Besides, the ETLSA strategy synergistically boosts ROS consumption through the superoxide dismutase (SOD)‐related pathways after SOD‐siRNA treatment. In conclusion, this SETLSA strategy with simultaneously blocking and dynamic monitoring oxidative stress has enriched the toolkit for promoting SCI repair.